STRUCTURAL DESIGN OF CONTAINER BERTH AT PORT OF BATU AMPAR, BATAM CITY, RIAU ISLANDS PROVINCE - Maulana, Fikri
Indonesia is an archipelagic country with very wide waters, so the role of maritime transportation is very important for the national economy and world trade. Port of Batu Ampar is one of the largest loading and unloading ports in Batam which supports industrial development in Batam as an international logistics hub, so that the movement of goods at the port increase every year. To overcome the problem of the existing condition of the port that cannot accommodate the increasing volume of loading and unloading, the development of the Port of Batu Ampar is carried out to improve loading and unloading services. This final project will discuss the structural design of container berth as a planning for the development of the Batu Ampar Port based on the design criteria used. The discussion in this final project includes environmental data processing, calculation of the load acting on the berth structure, determining the dimensions of berth and berth structural elements, structural analysis modeling, reinforcement of berth structural elements, and soil bearing capacity analysis. The available environmental data and operational data will be processed to calculate the load acting on the berth. Structural analysis modeling was carried out using SAP2000 software to determine the strength of the berth structure against the working load. The results of modeling in the form of Unity Check Ratio (UCR) values and structural deflections must meet the design criteria, namely the UCR value between 0.8 to 1 and the deflection value does not exceed the allowable deflection. Reinforcement of berth structural elements is carried out based on the internal forces obtained from the results of optimal structural analysis modeling. Soil bearing capacity analysis was also carried out to determine the required depth of piles needed to be able to withstand the load of the laying reaction on the berth structure. The result of this final project is plan consisting of dimensions of berth, dimensions of berth structural elements, reinforcement of berth structural elements, depth of berth piles.